First-principles study on the interfacial segregation at coherent Cu precipitate/Fe matrix interface. (August 2020) - Wang, Jingliang; Enomoto, Masato; Shang, Chengjia
Abstract: We present a systematic first-principles study on the segregation behavior of alloying element X (X=Al, Mn, Ni, and Si) at coherent body-centered cubic Cu precipitate/Fe matrix interfaces with three different orientations. The calculations predict a modest thermodynamic driving force favoring Fe/Cu interfacial segregation for Al, Mn and Ni and strong energetic preference of Si to partition to Fe matrix, consistent with experimental observation. The results give direct evidence that the interfacial segregation decreases the interfacial energy and explains the promotion of nucleation and retardation of coarsening of Cu precipitates by Al and Ni addition. Graphical abstract: Image, graphical abstract